2011
DOI: 10.1371/journal.pone.0017998
|View full text |Cite
|
Sign up to set email alerts
|

EndoG Links Bnip3-Induced Mitochondrial Damage and Caspase-Independent DNA Fragmentation in Ischemic Cardiomyocytes

Abstract: Mitochondrial dysfunction, caspase activation and caspase-dependent DNA fragmentation are involved in cell damage in many tissues. However, differentiated cardiomyocytes repress the expression of the canonical apoptotic pathway and their death during ischemia is caspase-independent. The atypical BH3-only protein Bnip3 is involved in the process leading to caspase-independent DNA fragmentation in cardiomyocytes. However, the pathway by which DNA degradation ensues following Bnip3 activation is not resolved. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
(86 reference statements)
0
28
0
Order By: Relevance
“…BNIP-3 and AIF cooperate to induce apoptosis and cavitation in epithelial morphogenesis [16]. Meanwhile, silencing BNIP-3 prevents Endo G translocation and DNA degradation [49]. We found that BNIP-3 protein levels and AIF and Endo G translocation were increased during cadmium-induced rPT cell apoptosis, while BNIP-3 silencing decreased AIF and Endo G translocation.…”
Section: Discussionmentioning
confidence: 98%
“…BNIP-3 and AIF cooperate to induce apoptosis and cavitation in epithelial morphogenesis [16]. Meanwhile, silencing BNIP-3 prevents Endo G translocation and DNA degradation [49]. We found that BNIP-3 protein levels and AIF and Endo G translocation were increased during cadmium-induced rPT cell apoptosis, while BNIP-3 silencing decreased AIF and Endo G translocation.…”
Section: Discussionmentioning
confidence: 98%
“…There have been several reports that AIF and EndoG translocate to the nuclei during neuronal and myocardial ischemia coincident with Bnip3 activation (Hamacher-Brady et al, 2006; Zhang et al, 2011; Zhang et al, 2007). In one of these, Zhang et al, (2011) reported caspase-independent, Bnip3-dependent release of EndoG in cardiac myocytes subjected to simulated ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these, Zhang et al, (2011) reported caspase-independent, Bnip3-dependent release of EndoG in cardiac myocytes subjected to simulated ischemia. Our studies suggest that AIF translocation accompanies Bnip3-mediated cell death during hypoxia/acidosis but this translocation is not dependent on Bnip3, mPTP, or calpains.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also mentioned that this resistance is no longer observed when cells are treated with ceramide or staurosporine, two apoptosis inducers acting through mitochondrial dysfunction, suggesting that this pathway could be involved in the induced neurodegeneration of cells affected by a TPP-1 deficiency [6]. The fact that BNIP3-mediated cell death was shown to be independent of caspase 3 and cytochrome c release in some cell types [24,62], argues in favour of a putative role of BNIP3 in the cell death observed in LINCL cells exposed to an external stress. As proposed by Zhao and co-workers, the BNIP3-mediated cell death would mainly involve the nuclear translocation of endonuclease G, an apoptotic DNase when released from mitochondria [63].…”
Section: Discussionmentioning
confidence: 99%